Management of mango weevil Sternochetus spp. (Coleoptera, Curculionidae) in Nagaland, India - Waluniba; Devi, H.S.; Neog, P.; Imtinaro, L.; Rokozeno; Maiti, C. (ENTOMON, 2026)
A field experiment was carried out in the farm of AICRP on Fruits,SAS:NU to evaluate the best treatments against mango weevil (Sternochetus spp.). The experiment was laid out in Randomized block designed using 7 different treatments. Among the different treatments, thiamethoxam (25% WG) gave the overall least mean number of incidence (1.17), with overall lowest mean per cent infestation (7.78). The treatment, thiamethoxam recorded highest overall yield (5.67 t ha-1) with maximum CB ratio (1:10.60).